Fluorescence Methods for Investigation of Living Cells and Microorganisms 2020
DOI: 10.5772/intechopen.93078
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Cell Viability Methods in 3D Scaffolds for Tissue Engineering

Abstract: Modern methods have evolved in tissue engineering to evaluate cell viability (CV) in 3D scaffolds and tissues. These involve either the usage of 3D confocal laser microscopy of live or fixed tissues, or separation of cells from the tissue, either live or fixed, and then their analysis by flow cytometry. Generally, working with live cells has the disadvantage that all the scanning needs to be completed immediately at the end of an experiment. Two different approaches can be distinguished: staining intact cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…25 Clinical data showed that the stiffness of native liver tissue increases drastically up to 4.1− 21.9 kPa during fibrosis due to aberrant ECM deposition, thus distorting angiogenesis and hepatic regeneration. 34 In our study, the compressive modulus was reduced in scaffolds possessing liver ECM compared to that in blank silk scaffolds and was similar to the healthy liver (1.5−4.5 kPa) (Figure 1H,I).…”
Section: Discussionsupporting
confidence: 68%
“…25 Clinical data showed that the stiffness of native liver tissue increases drastically up to 4.1− 21.9 kPa during fibrosis due to aberrant ECM deposition, thus distorting angiogenesis and hepatic regeneration. 34 In our study, the compressive modulus was reduced in scaffolds possessing liver ECM compared to that in blank silk scaffolds and was similar to the healthy liver (1.5−4.5 kPa) (Figure 1H,I).…”
Section: Discussionsupporting
confidence: 68%
“…Cytocompatibility of the matrix is typically assessed using live-dead staining. 92,93 Longer term continuous culture and estimation of proliferation rates by assays such as bromodeoxyuridine (BrdU), along with morphological assessments benchmarked against well-established 3D scaffolds or physiological samples, is also used to verify the suitability of a synthetic scaffold for 3D cell culture. 92,94…”
Section: B Biopolymers As Monolithic Bioink Substratesmentioning
confidence: 99%
“…Due to the impossibility of performing the Trypan Blue exclusion method on the printed cells, due to the hardening of the constructs by the crosslinking agent, the viability was evaluated using the LIVE/DEAD Viability Assay (ThermoFisher Scientific Inc., USA), which has already been used in different 3D bioprinting studies [52][53][54][55]. Constructs were incubated in 0.75 µM calcein AM (Invitrogen, Carlsbad, CA, USA) (green) and in 1 µM ethidium homodimer-1 (Invitrogen, Carlsbad, CA, USA) (red), dissolved in cold 1X PBS (Sigma-Aldrich, Milan, Italy).…”
Section: Viability Assaymentioning
confidence: 99%